An extended model of the theory of planned behavior to predict households response to net energy metering program in urban Malaysia - Sharifuddin, Shazleen Ilyana; Zainudin, Norzalina; Sabri, Mohamad Fazli (Human Resource Management Academic Research Society, 2022)
Malaysian government have seen solar Photovoltaic (PV) as one of the most promising renewable energy technology to combat climate change and decrease dependency of fossil fuels. At the end of 2016, Net Energy Metering (NEM) program has been implemented to encourage the use of solar PV to produce electricity in a greener way. However, the adoption rate for solar Photovoltaic (PV) under NEM Program among households still remain low. The factors of low participation of household in NEM program is an issue that need to be addressed. Therefore, in this research, the factors that affect household intention to adopt solar PV were studied, using Extended Theory of Planned Behaviour (ETPB) which consist of four variables which were attitude, subjective norm, perceived behavioural control and perceived cost. This study was conducted in the Klang Valley, Malaysia. The 500 questionnaires were distributed using non-probability stratified random sampling at the selected area in Klang Valley and yielded 410 respond rate. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to test the hypotheses. The results confirmed that attitude, subjective norm and perceived behavioural control have significant influence on intention to install solar PV. The findings also found that perceived cost has a positive influence on intention to install solar PV which differs from past studies. In the other words, perceived cost is not a barrier to the adoption of solar PV among household in Malaysia. Nevertheless, the findings have contributed towards the advancement of knowledge in the field of solar PV under the NEM program in Malaysia. Moreover, this study also contributes to the literature by adding new variable in TPB theory that are relevant to solar energy adoption. These findings also significantly contribute to those involved in the marketing of solar products.